2020
DOI: 10.1007/s41542-020-00058-1
|View full text |Cite
|
Sign up to set email alerts
|

Lost in Autonomy – Temporal Structures and Their Implications for Employees’ Autonomy and Well-Being among Knowledge Workers

Abstract: Conceptual models based on the importance of work autonomy for employees' health represent important cornerstones in the occupational well-being and work stress literature. The objectives of this study were to 1) explore and understand the temporal conditions framing work among autonomous knowledge professionals, 2) describe how autonomy is experienced in knowledge work jobs, and 3) analyze the implications of current autonomy for well-being in knowledge work. The interview study consisted of 21 women and 13 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…This result indicates that when employees with high job autonomy perceive high time-pressure, the positive relationship is strengthened. Väänänen, Toivanen, and Lallukka (2020) proposed that the role of job autonomy on employees' well-being is complicated. Job autonomy "can be both a resource and a burden" (p. 96).…”
Section: Discussionmentioning
confidence: 99%
“…This result indicates that when employees with high job autonomy perceive high time-pressure, the positive relationship is strengthened. Väänänen, Toivanen, and Lallukka (2020) proposed that the role of job autonomy on employees' well-being is complicated. Job autonomy "can be both a resource and a burden" (p. 96).…”
Section: Discussionmentioning
confidence: 99%
“…More than 55% of experts indicated that this category is vital for a KWr (advanced communication and negotiation skills (70%), interpersonal skills and empathy (95%), leadership and managing others (55%), entrepreneurship, and initiative-taking (70%), and mentorship and teaching skills (75%)). The KWrs are autonomous workers who perform interconnected tasks (Väänänen et al, 2020). In order to be successful in performing their daily activities, the KWrs must possess strong social and emotional competencies.…”
Section: Social and Emotional Skillsmentioning
confidence: 99%
“…A lifestyle intervention that consisted of adopting a healthy diet, increasing physical activity, and stress management improved depressive symptoms and quality of life in individuals with major depression [ 28 ]. In individuals with bipolar disorder, lifestyle interventions improved depressive symptoms, weight, physical activity, and serum lipids [ 29 ]. However, individual counseling aimed at reducing weight and increasing physical activity in middle-aged overweight or obese individuals with impaired glucose tolerance was not effective in reducing depressive symptoms [ 30 ].…”
Section: Discussionmentioning
confidence: 99%